Pelatihan Pembuatan Media Pembelajaran Interaktif Berbasis Android bagi MGMP Sejarah Lampung Selatan - Sumargono; Maskun; Aprilia Triaristina; Vany Aswandi (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2023)
Information Communication Technology (ICT) is one of the sub-sectors of technology that gave birth to many breakthroughs in the field of education in increasing the effectiveness and efficiency of the learning process. The use of ICT for education has become an option for various school institutions to increase efficiency in learning. The level of learning on the High School route, where the learning process is still relatively conventional (face to face), is actually no longer able to meet the increasingly complex educational needs of the community, requiring innovation and media that are able to cope with it. Android applications can be developed with a variety of software for developers. Android-based learning is expected to be one of the learning solutions, especially in the use of android-based historical learning media. Community service activities in the form of training and assistance in making history learning media at the Android-based high school level are carried out in two types, namely; 1) training activities, and 2) mentoring. The results of this community service activity are in accordance with the objectives of the activity, including: 1) History teachers at Senior High Schools in South Lampung Regency have been able to create android-based history learning media. 2) Teachers can implement android-based history learning media in history learning in the classroom. Based on the evaluation of the implementation of training and mentoring activities, it resulted in an increase in the ability of teachers in designing android-based historical learning media.